Improvement of Sonographic Appearance Using HAT-TOP Methods - Abdallah, Yousif Mohamed Y. (British Journal of Healthcare and Medical Research, 2018)
Ultrasound consider of one of the most important tool in analysis of fetus development. In ultrasound images, the recognition closely adjacent tissues is very crucial process because of the noise that affected both image quality and sharpness. This study conducted to study the fetus images improvement using HAT-TOP transform as computing choice in order to increase the diagnostic accuracy in diagnosis of neonatal diseases. Many image-processing techniques were used to improve the images including Using HAT-TOP and Blind Deconvolution Algorithm. The results of the study showed HAT-TOP was best processing filter and define the fetus precisely.